Severity of Liver Involvement in Children with Dengue Infection (Bangladesh Journal of Infectious Diseases, 2021)
Background: Liver involvement in dengue infection is one of the clinical presentations.Objective: This study was undertaken to see severity of liver dysfunction in children with dengue infection.Methods: It is a cross sectional observational study conducted in 100 consecutive children with serologically positive dengue infection aged between 2 months to 14 years of age. Liver function tests were done in all patients and were studied the severity of deranged LFT with severity of dengue infection.Results: Out of 100 admitted children with dengue infection, deranged liver function tests found in 57(57.0%). ALT was above normal in 10 (29.4% of DF, 19 (57.6%) cases of DHF and 19(57.6%) cases of DSS respectively. AST was above normal level in 12(35.3%) cases of DF, 23(69.7%) cases of DHF and 22(66.7%) cases of DSS respectively. Low albumin was found in 41.0% of cases, 15(45.5%) cases of DHF and 19(57.6%) cases of DSS. INR was high only 4 cases of DSS. The bilirubin was normal in all cases except one died due to ALF due to DSS. The mean ALT and mean AST statistically higher in DHF and DSS in compare to DF (P-value 0.011 and 0.037) respectively. However, there was no significant difference in meal ALT and AST between DHF and DSS respectively. Overall mortality in 2 cases with DHF and DSS.Conclusion: Dengue infection is associated with variable level of liver dysfunction. The severity of liver dysfunction can predict the severity of dengue infection.Bangladesh Journal of Infectious Diseases 2020;7(2):90-94